Penerapan Metode Pembelajaran Drill Berbantuan Media Cerita Bergambar untuk Meningkatkan Keterampilan Membaca Nyaring pada Siswa Sekolah Dasar - Maidini Tamara; Iis Aprinawati; Fadhilaturrahmi Fadhilaturrahmi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Study this aim for enhancement Skills read loud student class II SDN 014 Kuok year the 2022/2023 academic year, totaling 13 students . Method study this is Study Action Class (PTK) carried out in two cycle learning . Every cycle consist from two meeting and four Step learning namely : planning , implementation , observation and reflection . Time study held on month August 2022. Technique data collection in the form of documentation , observation and test . Results Skills read loud student class II SDN 014 Kuok on pre-action average value 52 ,30 with percentage 38% completeness . On cycle I meeting I average value 52.69 with percentage completeness study 38% and on Cycle I meeting II experienced enhancement with the average value is 56.15 with percentage completeness study 46%. On cycle II meeting I experienced enhancement also with the mean value is 61.53 with percentage completeness study 62% and on cycle II meeting II experienced enhancement again with the average value is 64.61 with percentage completeness learn 85%. With thereby could concluded that with application method learning drill story media help pictorial could increase Skills read loud student class II SDN 014 Kuok.